Preschool children's preferences for sedentary activity relates to parent's restrictive rules around active outdoor play - Nicola Wiseman; Neil Harris; Martin Downes (BMC, 2019)
Abstract Background With prevalence estimates indicating that young Australian children are increasingly sedentary, it is important to identify the relevant attributes that are shaping this lack of activity. Literature has identified safety concerns of parents as a consistent barrier to physical activity participation of young children. Despite safety being a plausible determinant of young children's activity preferences, the impact of restrictive parenting practices has rarely been examined through quantitative research. The current study investigates the link between controlling and supportive physical activity parenting practices and preschool children's physical activity knowledge, preferences and parent-reported behaviour. Methods The current cross-sectional study included 138 parent-child dyads and involved two components of data collection including a child and a parent questionnaire. Results of the parent and child questionnaires were matched to determine correlations between physical activity parenting practices and preschool children's physical activity knowledge, preference and parent-reported behaviour. Results Children's preferences for physical activity correlated with a number of demographic characteristics and physical activity parenting practices, with the most influential variables being parental age, parental rules around active play outdoors and parental use of screen-time to reward/control child behaviour. Based on parental-reporting, children who preferred to be physically active were more likely to engage in physical activity and were less likely to engage in screen-time on the weekend. Conclusions This study identified that parenting practices are not only associated with children's active and sedentary behaviours (parent-reported), but also with how children prefer to play (parent-reported). Future research should seek to clarify the relationship between children's activity preferences and parent's use of screen-time to reward and control their child's behaviour, given the developmental and behavioural health risks associated with excessive media/screen exposure in early childhood. Further research should investigate whether competing societal values of the importance of encouraging children's risky play and the need to prevent children from being injured, coupled with parent's busy schedules are contributing to parental ambivalence regarding how to promote active play for their children. Finally, research should be conducted to establish the relationship between physical activity parenting practices and children's objectively-measured activity level.